Clinico-epidemiological profile of thalassemia patients in a tertiary care center - Dr. Madhu Singh; Prof (Dr). R. Dayal; Prof (Dr). R. Dayal; Dr. Sheo Pratap Singh; Dr. L.K. Gupta; Dr. Madhu Nayak; Dr. Ram Kshitij Sharma; Dr. Akriti Yadav (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Thalassemias are inherited blood disorders characterized by abnormal hemoglobin production. There are two main types, alpha thalassemia, and beta-thalassemia. Beta Thalassemia Major (also called Cooley's Anemia) is a serious illness. Symptoms appear in the first two years of life and include paleness of the skin, poor appetite, irritability, and failure to grow. There is absent or decreased production of normal hemoglobin, resulting in microcytic anemia of varying degrees. The thalassemias have a distribution concomitant with areas where P. falciparum malaria is common. The alpha thalassemias are concentrated in Southeast Asia, Malaysia, and southern China. The beta thalassemias are seen primarily in the areas surrounding the Mediterranean Sea, Africa, and Southeast Asia. Proper treatment includes routine blood transfusions and other therapies which can lead to iron overload and contraction of infections such as HIV, HCV, and HBV shortening the life span of patients. On the other hand, inadequate transfusions may lead to severe anemia and debility.Material and Methods: This retrospective record-based cross-sectional study was conducted in S.N. Medical College, Agra.Results: In our tertiary center, we have 103 registered patients of thalassemia, in which 44 are females and 59 are males. Out of the 103 thalassemia cases, 95 (92.2%) belonged to beta-thalassemia major, 4(3.8%) of beta-thalassemia intermediate, and 1 (0.9%) of beta-thalassemia minor category. Fever was the most common presenting symptom. Pallor and hepatomegaly were the most common signs among cases.Conclusion: Hemoglobinopathies are the commonest hereditary disorders in India and pose a major health problem. The data on the prevalence of β-thalassemias and other hemoglobinopathies in different caste/ethnic groups of India is scarce.